THE EFFECT OF LISTENING TO THE QUR’AN (MUROTTAL) ON CHILDREN’S ANXIETY DURING HOSPITALIZATION IN THE PEDIATRIC WARDOF SARI ASIH KARAWACI HOSPITAL - Ici Sriwanti; Indra Tri Astuti; Nopi Nur Khasanah (LPPM Universitas An Nuur, 2026)
Background: Hospitalization in children can cause anxiety that negatively affects recovery and growth. One non-pharmacological intervention that may reduce anxiety is Qur’anic murottal therapy. This study aimed to examine the effect of listening to Surah Al-Ikhlas murottal on anxiety levels among hospitalized children in the Pediatric Ward of Sari Asih Karawaci Hospital. Methods: This quantitative study employed a one-group pretest–posttest design involving 38 children aged 6–12 years selected through accidental sampling. Anxiety levels were measured using the Indonesian version of the CSAS-C questionnaire before and after the intervention. The murottal therapy was administered for 20 minutes, twice daily for three days. Data were analyzed using univariate analysis and the Wilcoxon test. Results: Prior to the intervention, anxiety levels were predominantly classified as severe (36.8%). Following the intervention, anxiety levels decreased to a moderate level (44.7%). The Wilcoxon test indicated a significant difference in anxiety levels before and after the murottal therapy (p = 0.000). Conclusion: Listening to Surah Al-Ikhlas murottal therapy is effective in reducing anxiety among hospitalized children and may be recommended as a complementary non-pharmacological intervention in pediatric nursing care.